PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN MAHĀRAH KALAM SISWA MTS NURUL IMAN JAMBI - Abror, Ulil; Rahman; Neldi Harianto; Rofiazka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of students' mahārah al-kalām (Arabic speaking skills) at MTs Nurul Iman Jambi, characterized by limited vocabulary mastery, lack of confidence in speaking, and insufficient opportunities to communicate in Arabic during classroom instruction. This study aimed to describe the implementation of the Group Investigation (GI) cooperative learning model in improving the Arabic speaking skills of seventh-grade students. A qualitative descriptive approach was employed. The research subjects consisted of an Arabic language teacher and seventh-grade students. Data were collected through classroom observations, in-depth interviews, and documentation, and were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings revealed that the implementation of the Group Investigation model followed several stages, including topic selection, group formation, investigation planning, investigation activities, report preparation, presentation, and evaluation. The implementation of the model created a more active, collaborative, and communicative learning environment. Students demonstrated improvements in speaking confidence, vocabulary mastery, fluency, and active participation during Arabic learning. Furthermore, the model fostered collaboration, critical thinking, and self-confidence among students. Therefore, the Group Investigation cooperative learning model can serve as an effective alternative for improving Arabic speaking skills at the Madrasah Tsanawiyah level.